Diagnostic tests of microscopic and urine dipstick examination in children with urinary tract infection - Nurul Hidayah; Pungky Ardani Kusum; Noormanto Noormanto (Paediatrica Indonesiana, 2011)
Background Urinary tract infection (UTI) is common in childrenand, if incorrectly handled, may cause long-term complications,such as renal failure. The best test to diagnose UTIs is urineculture. However, urine culture is time-consuming, taking 3 - 5days. Therefore, there is a need for faster, alternative methods.Urinalysis is a common diagnostic test to establish the diagnosisof UTI.Objective To determine the sensitivity andspecificity of urine leukocytes, nitrite and leukocyte esterase forUTIs diagnosis.Methods We performed diagnostic tests at Dr. Sardjito Hospital,Yogyakarta. We examined the presence of leukocytes in urine by microscopy,urinary nitrite and leukocyte esterase by dipstick test, while comparing to urine culture as the gold standard.Results Two hundred children were included in our study. Byparallel test analysis, we found the sensitivity, specificity, positivepredictive value and negative predictive value of using all 3 testsin combination were 95%, 59%, 74% and 89%, respectivelyConclusion Test for urine leukocytes, nitrite and leukocyteesterase have high sensitivity but low specificity for diagnosingUTIs. Therefore, negative results in these 3 tests do not ruleout the possibility of UTI in children. [Paediatr Indones.2011 ;51;252-5].